Researcher Profile: Doug Hershey - Douglas A. Hershey (Journal of Financial Therapy, 2018)
Doug Hershey obtained his Ph.D. in Adult Development and Aging from the University of Southern California (1990). He is currently a Professor of Experimental Psychology at Oklahoma State University, where he also serves as Director of the Retirement Planning Research Laboratory. He has published more than 70 empirical articles on the development of life planning and decision making, with a special interest in the psychological factors that motivate individuals to plan for the future and save for old age. Hershey became a lifetime Fellow of the Gerontological Society of America in 2003, and in 2007 and 2015 he spent one-year terms as a Fellow-in-Residence at the Netherlands Institute for Advanced Studies (NIAS) in The Hague. When not working in the lab, Hershey can usually be found riding his bicycle through the beautiful rolling hills of North Central Oklahoma.